LABORATORIUM PEMBELAJARAN SENI TARI:RUANG KOLABORATIF UNTUK PENGEMBANGAN KREATIVITAS DAN PENELITIAN ARTISTIK DI PERGURUAN TINGGI - Umrintha, Dinna; Astuti, Fuji; Nerosti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The dance art learning laboratory is an important facility for developing creativity, research, and innovation in art education at the university level. This facility is not merely a place for physical practice or training; it also serves as a reflective and collaborative space that combines theoretical aspects, research, and artistic exploration. This conceptual study aims to analyze the role, function, and application of dance art learning laboratories in academic settings, particularly in the Master of Arts Education program. This research uses a conceptual approach with a literature review method thru analysis of relevant literature on art pedagogy, creativity, and learning innovation. The analysis results indicate that the dance art laboratory plays an important role in fostering esthetic sensitivity, critical thinking skills, and creativity among graduate students. Thru artistic research, creative reflection, and interdisciplinary collaboration, the dance art learning laboratory serves as the foundation for building an art education ecosystem that is adaptive, dynamic, and contextual. Keywords: learning laboratory, dance art, creativity, art education, higher education